Report on grading and pay, 1972-74 - Nigeria (Lagos : Federal Ministry of Information, Printing Division, 1974)
This reports highlights grades and payment recommended for federal government parastatals, including implementation procedures, detailed organizational and re-evaluation of jobs.
Cover title.
ahz 15/03/2019
Loans
Keywords: Civil service; Nigeria